Novel Roles of Amyloid-Beta Protein Precursor Metabolites in Fragile X Syndrome and Autism - Westmark, Cara J. (Mol Psychiatry, 2016)
Fragile X syndrome (FXS) is the most common form of inherited intellectual disability and is associated with up to 5% of autism cases. Several promising drugs are in preclinical testing for FXS; however, bench-to-bedside plans for the clinic are severely limited due to lack of validated biomarkers and outcome measures. Published work from our laboratories has demonstrated altered levels of amyloid-beta (Aβ) protein precursor (APP) and its metabolites in FXS and idiopathic autism. Westmark and colleagues have focused on β-secretase (amyloidogenic) processing and the accumulation of Aβ peptides in adult FXS models while Lahiri and Sokol have studied α-secretase (nonamyloidogenic or anabolic) processing and altered levels of sAPPα and Aβ in pediatric autism and FXS. Thus, our groups have hypothesized a pivotal role for these Alzheimer’s disease (AD)-related proteins in the neurodevelopmental disorders of FXS and autism. In this review, we discuss the contribution of APP metabolites to FXS and autism pathogenesis as well as the potential use of these metabolites as blood-based biomarkers and therapeutic targets. Our future focus is to identify key underlying mechanisms through which APP metabolites contribute to FXS and autism condition-to-disease pathology. Positive outcomes will support utilizing APP metabolites as blood-based biomarkers in clinical trials as well as testing drugs that modulate APP processing as potential disease therapeutics. Our studies to understand the role of APP metabolites in developmental conditions such as FXS and autism are a quantum leap for the neuroscience field, which has traditionally restricted any role of APP to AD and aging.